The revitalization of higher education: the IIUM as a model - AbuSulayman, AbdulHamid (IIUM Press, 2009)
Introduction: The solution to a given problem is often inappropriate or inadequate owing to an erroneous diagnosis or a defective analysis of the underlying causes. This applies in a real sense to the deficient diagnosis made for the underdevelopment of the Muslim ummah, an ailment from which it has been suffering for several centuries. One major reason for the failure of both the diagnosis and treatment has been that the emphasis has been hitherto placed on the symptoms rather than the underlying causes of the problems. Hence, appearances alone have been targeted in Muslims' attempts to remedy their condition.